2022
DOI: 10.3389/fcell.2022.844844
|View full text |Cite
|
Sign up to set email alerts
|

Non-Apoptotic Caspase Activity Preferentially Targets a Novel Consensus Sequence Associated With Cytoskeletal Proteins in the Developing Auditory Brainstem

Abstract: The auditory brainstem relies on precise circuitry to facilitate sound source localization. In the chick, the development of this specialized circuitry requires non-apoptotic activity of caspase-3, for which we previously identified several hundred proteolytic substrates. Here we tested whether the sequence of the caspase cleavage site differentially encodes proteolytic preference in apoptotic and non-apoptotic contexts. We constructed a consensus sequence for caspase activity in the non-apoptotic chick audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…However, it is unknown whether the same cleavage consensus sites are also used for nonapoptotic processes. In fact, recently, it was shown that Caspase-3 changes its preferred consensus site during a non-apoptotic process in the developing auditory brainstem in the chick embryo 38 . Likewise, if initiator caspases are incorporated into different protein complexes, they may have a different specificity and thus may cleave at different consensus sequences.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether the same cleavage consensus sites are also used for nonapoptotic processes. In fact, recently, it was shown that Caspase-3 changes its preferred consensus site during a non-apoptotic process in the developing auditory brainstem in the chick embryo 38 . Likewise, if initiator caspases are incorporated into different protein complexes, they may have a different specificity and thus may cleave at different consensus sequences.…”
Section: Discussionmentioning
confidence: 99%